An Intriguing Case of Angiomatous Meningioma Mimicking a Hemorrhagic Metastasis - Shrestha , Neha; Shrestha , Oshan; Gurung , Ayeshna; Khatiwada , Sameen (Journal of Nobel Medical College, 2024)
Meningiomas comprise a family of neoplasms derived from the meningothelial cells of the arachnoid mater. Peritumoural cerebral oedema can be prominent with certain histological subtypes, such as secretory, angiomatous/microcystic, lymphoplasmacyte-rich, and high-grade meningiomas. We report one such case presenting in our institute that showed well defined blood density hyperdense lesion of size 3.1x2.9x3.4 cm with marked perilesional edema in right parafalcinefronto-parietal lobe and was thought to be a hemorrhagic metastatic lesion or a primary glioma on CT as well as MRI scans. The histopathology however revealed it to be an angiomatous meningioma.